2RPS/2SPS Parallel Mechanism and Kinematics Analysis - Zhou Yijun; Chen Yefu; Su Ronghai (Jixie chuandong)
Based on constraint spiral theory，the modified Grübler-Kutzbach formula is used to analyze the degree of freedom of 2RPS/2SPS parallel mechanism. The inverse positional solution equation is established by the space coordinate transformation equation and the closed vector method，and the forward position problem is performed by Newton iteration method in numerical analysis based on inverse solution. The first-order influence coefficient matrix is established by the fictitious mechanism method，and the numerical example is verified by the differential method based on Matlab. The results show that the calculation results of the two methods are consistent. Finally，Adams software is used to conduct kinematic simulation of the 2RPS/2SPS parallel mechanism，and the displacement，velocity，acceleration and angular velocity change curves are obtained，which further verifies the correctness of the operation results of the first two methods. It also indicates that the 2RPS/2SPS parallel mechanism has good motion characteristics.